Evaluation of the efficacy and safety of a new device for eye drops instillation in patients with glaucoma - Junqueira DM (Dove Medical Press, 2015)
Daniela M Junqueira,1 Flavio S Lopes,1,2 Fabiola C de Souza,1 Syril Dorairaj,3 Tiago S Prata1,21Glaucoma Unit, Hospital Medicina dos Olhos, Osasco, Brazil; 2Department of Ophthalmology, Federal University of São Paulo, São Paulo, Brazil; 3Department of Ophthalmology, Mayo Clinic, Jacksonville, FL, USAObjective: This study evaluated the efficacy and safety of a new device (Eyedrop®) designed for eye drop instillation in patients with and without glaucoma.Methods: This prospective study included consecutive patients with glaucoma and healthy participants. After a complete eye examination and determination of baseline intraocular pressure (IOP), topical hypotensive medication was introduced in both eyes, and the Eyedrop® delivery device (a plastic device in which the bottle with eye drops is inserted) was made available to all participants (with video and written instructions) for use in one eye, randomly chosen. In the second phase, all patients were evaluated by an experienced examiner for IOP determination, investigation of possible associated side effects, and ease of instilling eye drops (by a visual analog scale [VAS]; 0–10).Results: Thirty two participants (mean age 42.3±16.2 years) were evaluated. Of these, 44% had glaucoma. There was no significant difference in mean IOP variation when comparing the eye using (-3.9±2.9 mmHg) or not using the device (-3.3±2.6 mmHg; P=0.36). The subjective rating of the facility of drops instillation was significantly higher with the Eyedrop® applicator (VAS =7.6±1.6) than without it (VAS =6.2±1.8; P<0.01), with a higher frequency of positive device-related evaluations (VAS score >5) among participants without prior experience with eye drop instillation (78.6% [11/14]) versus those already experienced (66.7% [12/18]). No difference in the frequency of side effects or in the distribution pattern of fluorescein between eyes was observed (P≥0.63).Conclusion: Eyedrop® received a better subjective response regarding the ease of instillation of hypotensive eye drops compared to traditional instillation, especially in patients with no previous experience with eye drops. Using the device did not result in any loss of hypotensive effect or increase in the frequency of side effects.Keywords: glaucoma, eye drops, applicator, therapy adherence